Endoscopic Analysis of Microstructures of the Colon Mucosa on the Edge of the Post-Resection Defect as a Measure of Preventing Recurrence of Polyps after a Cold Polypectomy - N. V. Ageykina; N. A. Oleynikova; P. G. Malkov; N. V. Danilova; O. A. Kharlova; Yu. M. Korolev; E. D. Fedorov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2020)
The aim of this study was to assess the usefulness of endoscopic removal of small (less than 10 mm) colon polyps with a cold snare on the basis of endoscopic microstructural analysis of the edges of the post-resection defect using high-resolution video endoscopic equipment.Methods. In 74 patients (22 men and 52 women) aged 28 to 84 years (average age 59.3 ± 3.6 years), 103 colon polyps of types 0-IIa — 82 (79.7 %) and 0-Is — 21 (20.3 %), without the signs of severe dysplasia and cancer, were removed through the endoscope by the using of a cold snare, followed by mandatory inspection of the edges of the post-resection defect. A complete endoscopic analysis of the microstructures and the capillary vessels of the mucosa was performed on the edge of the post-resection defect, and then was compared to the histological image.Results. The endoscopic criteria for completely performed cold snare resection were identified, they are parallel crypts and the structure of intestinal pits of type I (S. Kudo) in the edge of the post-resection defect, which were observed in 93 (90.3 %) cases. Signs of residual tissue were dilated altered crypts with a violation of the parallelism of their location, which were observed in 10 (9.7 %) cases. The difference between the spatial location of crypts in the rectum (the effect of “falling crypts”) was identified, which complicates the differential diagnosis of normal and residual tumor tissue. In the endoscopic diagnosis of the vascular pattern of the colon mucosa was determined that flat-elevated polyps have a fine capillary network, which reduces the risk of bleeding when use a cold resection method. An observation (diagnostic colonoscopy) was performed in 11 (10.7 %) patients, including a case with the polyp with high grade displasia. No advance adenomas and interval cancers were detected.Conclusion. Тhis research helps to ensure reliable diagnosis of the completeness of performed endoscopic intervention and the possibility of removal of residual tumor tissue (if present) immediately after its completion, it’s allow a reduction in the number of recurrences of tumors.